2010
DOI: 10.1007/s00415-010-5843-6
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility weighted imaging: does it give information similar to perfusion weighted imaging in acute stroke?

Abstract: Dear Sirs,In a patient presenting with acute stroke it is essential to make a quick decision on thrombolysis based on history, clinical findings and the information obtained on an urgent CT or MRI. Though CT is considered the imaging technique of choice to rule out intracerebral haemorrhage, MRI using a gradient T2*/SWI sequence has been found to be equally good [1]. If the presentation is beyond the first 3 h, there is a need to image the salvageable penumbra. MRI gives information about the penumbra by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 7 publications
4
38
0
Order By: Relevance
“…[9][10][11][12][13]15 SWI may do the following: 1) detect hemorrhagic components within infarcted tissue with higher sensitivity than other MR imaging sequences or imaging modalities, 16 2) demonstrate hypointense signals in the veins draining hypoperfused areas and evaluate the ischemic penumbra by focusing on the venous drainage, [9][10][11][12] 3) show hyperintense signal in the veins draining regions of hyperperfusion or luxury perfusion indicating an increased risk of developing postischemic malignant edema, 13 4) detect acute occlusive arterial thromboemboli, 17,18 5) quantify microhemorrhages and predict hemorrhagic transformation before thrombolytic therapy is initiated, 19 and 6) detect early hemorrhagic complications after intra-arterial thrombolysis. 17 Currently, most studies focus on adults, and literature on the role of SWI in PAIS is scant, based mostly on case reports or small case series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13]15 SWI may do the following: 1) detect hemorrhagic components within infarcted tissue with higher sensitivity than other MR imaging sequences or imaging modalities, 16 2) demonstrate hypointense signals in the veins draining hypoperfused areas and evaluate the ischemic penumbra by focusing on the venous drainage, [9][10][11][12] 3) show hyperintense signal in the veins draining regions of hyperperfusion or luxury perfusion indicating an increased risk of developing postischemic malignant edema, 13 4) detect acute occlusive arterial thromboemboli, 17,18 5) quantify microhemorrhages and predict hemorrhagic transformation before thrombolytic therapy is initiated, 19 and 6) detect early hemorrhagic complications after intra-arterial thrombolysis. 17 Currently, most studies focus on adults, and literature on the role of SWI in PAIS is scant, based mostly on case reports or small case series.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous reports have shown that SWI-hypointense signals in veins draining hypoperfused brain areas provide indirect evaluation of critically perfused tissue by focusing on venous drainage. [9][10][11][12] In addition, SWI-hyperin-tense signal was reported to detect regions of hyperperfusion and to be associated with an increased risk of developing postischemic malignant edema. 13 SWI may consequently serve as a valuable alternative sequence to evaluate the hemodynamics of brain tissue in PAIS.…”
mentioning
confidence: 99%
“…[1][2][3][4] The presence of microhaemorrhage, prominent veins and susceptible vein sign on SWI series has been applied for evaluating stroke severity, treatment response and prognosis. [5][6][7][8] Asymmetrically dilated cortical and medullary veins on SWI have been reported in patients with acute ischaemic stroke.…”
Section: Introductionmentioning
confidence: 98%
“…The cortical vessel signs (CVSs) on susceptibility-weighted magnetic resonance images (MRIs) have been reported to be indicative of acute cerebral artery occlusion and well correlated with the amount of deoxyhemoglobin in the venous and capillary compartments [1,2,3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…The prominence is thought to be due to increased deoxyhemoglobin in the veins. This may be secondary to increased oxygen extraction fraction (OEF) due to reduced blood flow [1,2,5,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%